The Effect of Multipass Strategy and Students’ Attitude Toward Their Reading Comprehension at the Tenth Graders of SMAN 2 Lubuk Alung - Desrimayuti Desrimayuti (JURNAL ARBITRER, 2019)
This study aims to determine the effect of multipass strategies and student attitudes on students' reading comprehension in historical recount texts. The design of this research is Quasi Experiment Research with a 2x2 factorial design. The population of this research is the students of class X SMAN 2 Lubuk Alung Academic Year 2018/2019. Reading tests and student attitude questionnaires were used as research instruments. Then, the research data were analyzed using the T-test formula and Two-Way ANOVA. The results of this study indicate that (1) students taught with multipass strategies have better reading scores than students taught with ordinary strategies, (2) students taught with multipass strategies with positive attitudes have better reading values than students taught with ordinary strategies, (3) students taught with multipass strategies with negative attitudes have better reading scores than students taught with common strategies, and (4) there is no interaction between the two teaching strategies (multipass strategies and ordinary strategies) and students 'attitudes towards students' reading comprehension.